Rate and Risk Factors of Complicated Appendicitis: 3-Year Insights and Outcomes of Appendicectomy - Dr. Jabar Kadhim Jassim; Alaa sherif Ibrahim; Haider Kadhim Abdulrazzaq Almohsin (Open Journal of Physicians and Surgeons, 2024)
Background: Acute appendicitis (AA) still represents a challenging surgical emergency the surgeons face on their daily clinical practice. Appendicectomy is the safest familiar surgical procedure, in particular when it performed by experienced professional surgeons. Although acute appendicitis is common on daily practice, the rate and risk factors of progression to complicated appendicitis are still not well addressed particularly in Iraq. Aim of study: To estimate the rate of complicated appendicitis and its main risk factors and predictors among Iraqi patients Patients and Methods This was a prospective study of cross-sectional design with analytic utility conducted at Al Shifaa General Hospital in Basra city, south of Iraq, data collection and patients enrollment started since the year 2022 through 2024. A total of 354 patients who were operatively managed were enrolled during the study period. Preoperatively, all patients were well prepared according to the standard clinical guidelines. Intraoperatively, appendicitis was classified by the surgeon as complicated or uncomplicated. Patients were followed for at least 30 days after surgery. Results: The rate of complicated appendicitis was 20.3%. The main risk factors for complicated appendicitis were older age, delayed presentation, presence of comorbidities, male gender and obesity; the odds ratio for these factors was 3.254, 2.829, 2.667, 1.970 and 1.863, respectively. Positive findings of Ultrasound and CT scan, Leukocytosis (WBC count > 10000 /µL) and higher C-reactive protein were good predictors of complicated AA. Postoperative complications and readmission rates were higher in patients with complicated AA than those with uncomplicated. Conclusions: Complicated appendicitis reported in a rate of 20.3% of acute appendicitis cases. Older age, delayed presentation, presence of comorbidities, male gender and obesity were the main significant risk factors for complicated appendicitis.